Energy Sources from Agriculture and Rural Areas - Krupin, Vitaliy; Podolets, Roman (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is a complimentary work of over 70 scholars from various countries, including Poland, Ukraine, and the Czech Republic. The issues analyzed in the 16 articles primarily focus on energy generation in rural areas, particularly in the agricultural sector. They examine specific crops or livestock production and range from case studies of individual countries to the level of the European Union. Published works collectively review the economic and environmental issues of energy generation. These include the potential of agricultural production to serve as a resource for bio-energy generation, the economic and energy efficiency of farms and rural residential housing, and the impact of agricultural production on greenhouse gas emissions. They also explore the possibility for farms to achieve energy self-sufficiency, as well as the progress and gaps in the development of renewable energy generation.